Dampak Area Tugas Dan Tunjangan Jabatan Pada Performa Perangkat - Madiyah Tri Cahayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the impact of task areas and position allowances on device performance in an organization. The research method uses a quantitative approach by collecting data through surveys and statistical analysis. The research sample involved a number of officers at various levels of positions in representative organizations. Task area variables are identified and classified, while position allowances are evaluated based on the type and amount received. The results of the analysis show that there is a significant relationship between the task area and position allowances and device performance. The implications of these findings can help organizations design more effective policies regarding the management of job duties and benefits to improve device performance.